OPERATIONAL MECHANISM OF KARST SPRING “LOGARAS”, NEAR THE VILLAGE “SKORTSINOU”, ARCADIA, (PELOPONNESUS) - Karalemas, N.; Lekkas, S. (Bulletin of the Geological Society of Greece, 2010)
This paper presents information on the behavior of the Logaras karst spring, which is located 2.5 km north of Skortsinou village of the Municipality of Falaesia. This spring discharges the water table hosted in the carbonate rocks located in the area among Skortsinou, Petrina, Soulario and Voutsaras Villages. This area consists of thin-platy limestones of Pindos Unit that overlay the “First Flysch” formation, which is the stratigraphic bedrock of the aforementioned limestones. Aiming at the accurate determination of the boundaries of the spring’s hydrological basin, the geological map of I.G.M.E., sheet “Megalopolis” (Papadopoulos 1997 και Luettig & Vingen 1964) was re-examined. The geological and tectonic observations that derived from this process contributed to the analysis of the spring’s mechanical operation. This led to the conclusion Logaras Spring is a contact spring. Furthermore, discharge measurements of the spring took place for the period from 24/6/2006 to 26/10/2007 and the relevant hydrograph was drawn, from which the recession coefficient was calculated. More particularly, the spring’s recession coefficient for the hydrological years 2005 – 2006 and 2006 – 2007 is 1,9·10-3 and 4,3·10-3 respectively, while the dynamic volume reach 5,4 • 106 m3 and 1,7 • 106 m3 respectively.